2012
DOI: 10.1186/1756-0500-5-254
|View full text |Cite
|
Sign up to set email alerts
|

Late somatic sequelae after treatment of childhood cancer in Slovenia

Abstract: BackgroundThis is a long-term follow-up clinical study of adolescents and adults, survivors of childhood cancer. We evaluate and analyze the late somatic sequelae of childhood cancer treatment. Many such studies are susceptible to a strong selection bias, i.e., they employ a limited non-systematic sample of patients, based on a clinical hospital that provided the cancer treatment or performed the follow-up. To address the issue of selection bias, we perform here an analysis of late sequelae on a systematic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Comparison to the SJLIFE adapted CTCAE for grading of clinically ascertained data showed that more of our core outcomes were missing and that 24 clinically relevant conditions corresponded to grade 2 or even grade 1. Hence, our results support previous authors, concluding that the CTCAE in its current form is not optimal to grade severity of (self-reported) long-term physical morbidity outcomes for CCS [ 41 43 ]. To our knowledge, this is the first comprehensive proposal to define a core outcome set for self-reported long-term physical outcomes in CCS.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Comparison to the SJLIFE adapted CTCAE for grading of clinically ascertained data showed that more of our core outcomes were missing and that 24 clinically relevant conditions corresponded to grade 2 or even grade 1. Hence, our results support previous authors, concluding that the CTCAE in its current form is not optimal to grade severity of (self-reported) long-term physical morbidity outcomes for CCS [ 41 43 ]. To our knowledge, this is the first comprehensive proposal to define a core outcome set for self-reported long-term physical outcomes in CCS.…”
Section: Discussionsupporting
confidence: 88%
“…Because the CTCAE criteria were originally designed for grading acute adverse events during adult cancer trials [ 54 ], the current CTCAE version 4.03 [ 40 ] does not cover the complete spectrum of long-term morbidity that CCS might encounter [ 42 ]. Several authors have already stated that relevant outcomes were missing for CCS and use adapted versions [ 41 43 ]. Comparison of our core set of long-term self-reported physical outcomes to the commonly used CTCAE showed that 36% of the outcomes were not present in the CTCAE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest data from EUROCARE-5 focused on adolescents and young adults diagnosed between 2000 and 2007 exhibited improved survival in children and adolescents, but relatively poorer in adolescents and young adults than in children [ 31 ]. Similarly, in a Slovenian study, older age at diagnosis decreased the risk for late sequelae [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…An American multi-institutional study reported that over 60% of cancer survivors after oncology therapy in childhood had at least one, and 20% had multiple chronic health conditions [4, 6]. Observations from Europe are similar and show that more than 50% of the survivors present at least one side effect, with a growing prevalence and severity with time after the completion of oncology treatment [2, 710]. The nationwide study performed in the largest cohort of Polish childhood cancer survivors showed that over 80% of them had one or more symptoms of organ dysfunction [11].…”
Section: Introductionmentioning
confidence: 99%